Laser beam decontamination of metallic surfaces with a pulsed (150 W) Nd:YAG laser - Anne-Maria Reinecke; Margret Acker; Steffen Taut; Marion Herrmann; Wolfgang Lippmann; Antonio Hurtado (Nuclear Engineering and Technology, 2023)
Laser decontamination of radioactive surfaces is an innovative technology. Our contribution to improving this technology includes studies on laser beam decontamination with a pulsed laser of an average power of 150 W, equipped with a hand guided working head. Our investigations are focused on metallic surfaces typical in nuclear power plants, such as stainless steel, bright and rusted mild steel, galvanized steel, and painted steel. As typical nuclides of contaminated surfaces we chose Co-60 and Cs-137, the most frequently occurring nuclides in many nuclear plant components; Sr-85 as a representative of Sr-90, the potentially most harmful fission nuclide; and Am-241 as a representative of the minor alpha-radiation emitting actinides. Here, we present our results of decontamination and recovery ratios. Decontamination ratios of 90–100% were achieved on different surfaces.